Patterns of Self-Medication with Ophthalmic Drugs and Associated Determinants among Patients Visiting Ophthalmology Clinics - Fayaz Ahmed Soomro, Abdul Qadeem Soomro, Abdul Sattar, Syed Saifullah Shah, Ali Mujtaba Shah, Abdullah Laghari, Anas Bin Tariq, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Worldwide, use of self-medication (SM) is highly common, leading to inappropriate use of medications. Objectives: To determine the prevalence and pattern of self-medication and their associated determinants in patients attending Ophthalmology clinics Methods: A cross sectional analytical research using non-probability consecutive sampling technique was carried out for six months (April 2023 to September 2023) at the out-patient department (OPD) of Ophthalmology department of a tertiary care hospital in Karachi, Pakistan. 195 patients >18 years of age, visiting the ophthalmology OPD during study time period and providing informed consent for participating in the research were included. SPSS v23.0 was used for data analysis. Association was reported between various factors and SM keeping p<M0.05 statistically significant. Results: Among 195 ophthalmic patients, 45.1% (n=88) reported practicing self-medication with eye medications. Antibiotics were the most commonly used drugs, followed by corticosteroids. Eye redness and foreign body sensation were the main symptoms prompting self-treatment. Easy access to medications and previous experience were the leading reasons for this practice, while pharmacy professionals were the primary source of information guiding self-medication. Awareness and attitude both were significantly associated with SM. Conclusion: Self-medication with ophthalmic drugs was common among patients, largely driven by easy access to medications and prior experience, highlighting the need for stricter regulation and increased patient awareness to promote safe use of eye medications. Keywords: Drug accessibility, Self-Medication, Ocular Health, Ophthalmic Drugs.